Prophylaxis Against Mycobacterium avium Complex Infection in AIDS - DW Cameron (Canadian Journal of Infectious Diseases)
Disseminated Mycobacterium avium complex (MAC) infection in AIDS is increasing in frequency, although it remains under-recognized due to unlocalized clinical manifestations and subtle initial presentation, if not the need for specialized laboratory diagnostic methods. Ultimately, MAC accounts for much of the “wasting syndrome” in the natural history of human immunodeficiency virus disease. Multidrug treatment of MAC in AIDS is problematic. That MAC is preventable has been demonstrated, and how much clinical benefit can be had from successful prophylaxis remains to be evaluated in the face of improved efficacy of both treatment and prophylaxis regimens under investigation.